THE GENERAL APPROACH TO THE ECONOMIC EVALUATION OF THE STRUCTURE OF THE RAILWAY STATION - Safronenko, O. O. (Science and Transport Progress, 2008)
The main criteria for a choice of block diagram of the railway station accepted to the further design are its technical, technological and economic validity. In the given article all three criteria necessary for decision-making on efficiency of this or that block diagram are considered. The special attention is paid to economic estimation of alternative structures of stations synthesized in an automated mode.